Prevalence of gallstones among gastric sleeve patients in Saudi Arabia - Suliman, Osman Elamin A.; Alsaedi, Emad Abdulrahman H.; Albalawi, Haya Zaki H.; Alshanqiti, Zainab Abdullah A.; Alrehaili, Meaad Abdulaziz; Aloufi, Hussam Khalid; Alsubhi, Reham Mohammed; Aljayyar, Mohammed Waleed (International Journal Of Community Medicine And Public Health, 2025)
Background: Gallstones are a common condition affecting millions of individuals worldwide, with obesity being one of the significant risk factors. In Saudi Arabia, the prevalence of obesity is high, and sleeve gastrectomy is one of the leading solutions used to reduce weight. Studies have found that sleeve gastrectomy results in increased onset of gallstones. This study aims to investigate the prevalence of gallstones among gastric sleeve patients in Al-Madinah and Al-Munawara. Methods: The data was collected through an online questionnaire. A cross-sectional study will be conducted among 380 participants. The data was analyzed using SPSS with descriptive statistics, paired sample t-test, chi-square test, and correlation test. Results: There were 380 participants, with a mean age of 30.48±7.98 years, out of which 51.6% developed gallstones after the gastric sleeve procedure. The data revealed a significant decrease in body weight and BMI after gastric sleeve, and risk factors such as obesity, cholecystitis, pancreatitis and liver hematoma were positively correlated with the onset of gallstone after gastric sleeve. Conclusions: The prevalence of gallstones after gastric sleeve is notably high, so pre-operative and post-operative management should be emphasised, and further research on a larger scale should be done.